High‐gain miniaturized magnetoelectric dipole antenna array for millimeter‐wave applications. Issue 6 (19th January 2023) - Wang, Kaize; Sun, Yurong; Meng, Wenwen; Xu, Juan
Abstract: In this paper, a miniaturized high gain magnetoelectric dipole (MED) antenna array is proposed, which is composed of a one‐to‐two‐way substrate‐integrated waveguide  E ‐plane T‐type waveguide power divider as the feeding network. The MED antenna consists of a pair of mirror‐symmetrical E‐patches and a pair of vertical metallized vias. The size of the antenna array is 1.2 λ 0 × 1.6 λ 0 × 0.17 λ 0 . A bandwidth of 29.3% (25.6–34.4 GHz) for S 11 < −10 dB can be achieved and has unidirectional radiation performance in the operating frequency band. The peak gain of the antenna reaches 11 dBi, and the average gain can reach more than 10 dBi.